Clinical efficacies of different neoadjuvant therapies for non-small cell lung cancer - Xin-chen Tan; Xin-yun Song; Meng-qi Jiang; Neng-yang Wang; Jun Liu; Wen Yu; Qin Zhang; Xu-wei Cai; Wen Feng; Xiao-long Fu (Translational Oncology)
Neoadjuvant therapy followed by surgery is a common clinical strategy for operable non-small cell lung cancer (NSCLC), and the mainstream neoadjuvant therapies include chemoimmunotherapy, targeted therapy, and chemotherapy. However, there is a lack of studies to report the difference in benefits between these treatment modalities in the same institution. Therefore, this study aimed to depict the short-term efficacy of radiology and pathology achieved by different therapies and their impact on long-term survival as well as the underlying clinical significance. A total of 243 NSCLC patients who underwent different neoadjuvant therapies were eligible for inclusion. Demographic, radiological, and pathological features of patients were recorded. The event-free survival (EFS) outcome was analyzed using Kaplan-Meier analysis. The objective response rates (ORR) of primary tumor in the chemoimmunotherapy, targeted therapy, and chemotherapy cohorts were 48.95 %, 57.58 %, and 34.09 % respectively, major pathological response (MPR) rates were 58.74 %, 15.15 %, and 20.83 % (P<.0001), and pathological complete response (pCR) rates were 41.26 %, 0 %, and 11.11 % (P<.0001). For consistency between imaging and pathological evaluation, Cohen's Kappa were 0.275, 0.233, and 0.330. The EFS of MPR group was significantly longer than that of non-MPR group in the chemoimmunotherapy and chemotherapy cohorts (P=.0077**&.0343*, HR=0.3287&0.3715), but this improvement was not observed in the targeted therapy cohort. Neoadjuvant chemoimmunotherapy often underestimates pathological efficacy in imaging but shows consistent long-term outcomes. Neoadjuvant chemotherapy with moderate overall effectiveness has a significant correlation between short-term benefits and reduced recurrence. Neoadjuvant targeted therapy shows remarkable short-term imaging improvements but often fails to convert into sustained long-term survival.